Website Mahasiswa Program Studi Teknik Informatika Menggunakan Metode Scrum - Gideon Febri Tuuk; Ferdinan I. Sangkop; Vivi Peggie Rantung (Pusat Riset dan Inovasi Nasional, 2023)
This research study uses the Scrum method. This method is a method related to how to conduct studies with agile software development. Scrum is a method whose evaluation can provide good results for the software processor on the computer to increase one's curiosity to always act as a user in the computer applications that are running. The activities carried out include the creation of product backlogs, sprint backlogs, daily scrums, sprint reviews, and sprint retrospectives. Scrum participates. Scrum owns the application being run, including the Scrum Master and the development team. The stages or steps that are carried out in Scrum are well managed and structured to achieve good results and are fun to use, use them effectively and efficiently so that it creates a feeling of pleasure for users when operating them and results that will be developed next can use existing systems and use things according to the evaluation or procurement according to the needs of the user. The findings from the activity of developing a Website-based Delivery Order application using the scrum method have proven that existing problems can be easily resolved by changing the requirements in the state of the system group, providing results that are in line with the desired needs realized by the user and direct assessments can be held shortly after using the held device.